Investigations of a noise control of a plate with four pairs of piezoelectric elemen - Wiciak, J. (Archives of Acoustics, 2006)
The paper explores the potentials of reducing the amplitude of plate vibrations and radiated noise through the use of piezoelectric actuators in an asymmetric configuration. Tests were run on a aluminium plate, bonded on one edge. On one of the surfaces there were four piezoelectric actuators, on the other surface there were four piezoelectric sensors. One of the actuators served as vibrations generator, while the remaining were used for vibration control. The influence of the actuators activation and shape form on the structure’s response are investigated. The finite element method analysis was performed, with the application of the ANSYS computer package, and then obtained results were confirmed experimentally.